Wearable Device for the Detection of COVID19 using Internet of Things - Deepshika S
The basic concept of the proposed work wearable Device for detecting COVID-19 is that people can wear it instead of being carried supplements. The wearable device in the market is more general health monitoring and has different sensors in different wearables. The idea behind the device's development is to provide better care for patients and people to detect the covid at the earliest to take up tests and save society from the impact of the pandemic. Patients can continuously monitor their health after the covid19 infection to have better knowledge about their recovery. The primary purpose is to quarantine the affected patients by providing treatment and to avoid a public crisis by spreading it to others.